Preparation and in‐vitro/in‐vivo evaluation of curcumin nanosuspension with solubility enhancement. (10th June 2016) - Li, Xin; Yuan, Huiling; Zhang, Caiyun; Chen, Weidong; Cheng, Weiye; Chen, Xin; Ye, Xi
Abstract: Objectives: We developed Cur nanosuspension (Cur‐NS) with PVPK30 and SDS as stabilizers to improve poor water solubility and short biological half‐time of Cur. Methods: Physicochemical characterization of Cur‐NS was characterized systematically. The in‐vitro dissolution, cytotoxicity and in‐vivo pharmacokinetic experiments of Cur‐NS were also evaluated. Key findings: Scanning electron microscope indicated that the morphologies of Cur‐NS were spherical or ellipsoidal in shape. X‐ray diffraction verified that Cur was successfully developed as nanoparticles with an amorphous phase in Cur‐NS. Fourier transform infrared spectroscopy suggested there was no degradation about Cur in the Cur‐NS. Furthermore, the in‐vitro study showed that the cumulative release of the Cur‐NS was 82.16 ± 2.62% within 34 h and the cytotoxicity of the Cur‐NS against HepG2 cells was much better than raw Cur. Besides, in‐vivo pharmacokinetics in rats by intravenous injection displayed that the in ‐ vivo process of Cur‐NS pertained to two‐compartment model. Meanwhile, the t 1/2 and AUC0– t of Cur‐NS were enhanced by 11.0‐fold and 4.2‐fold comparing to Cur solution. Conclusions: The Cur‐NS significantly increased the water solubility and half‐time of Cur, suggesting its potential as a nanocarrier in the delivery of Cur for future clinical application.